Investigating Intestinal Barrier Breakdown in Living Organoids - Bardenbacher, Marco; Ruder, Barbara; Britzen-Laurent, Nathalie; Naschberger, Elisabeth; Becker, Christoph; Palmisano, Ralf; Stürzl, Michael; Tripal, Philipp (Journal of Visualized Experiments, 2020)
Organoids and three-dimensional (3D) cell cultures allow the investigation of complex biological mechanisms and regulations in vitro, which previously was not possible in classical cell culture monolayers. Moreover, monolayer cell cultures are good in vitro model systems but do not represent the complex cellular differentiation processes and functions that rely on 3D structure. This has so far only been possible in animal experiments, which are laborious, time consuming, and hard to assess by optical techniques. Here we describe an assay to quantitatively determine the barrier integrity over time in living small intestinal mouse organoids. To validate our model, we applied interferon gamma (IFN-gamma) as a positive control for barrier destruction and organoids derived from IFN-gamma receptor 2 knock out mice as a negative control. The assay allowed us to determine the impact of IFN-gamma on the intestinal barrier integrity and the IFN-gamma induced degradation of the tight junction proteins claudin-2, -7, and -15. This assay could also be used to investigate the impact of chemical compounds, proteins, toxins, bacteria, or patient-derived probes on the intestinal barrier integrity.
CRIS-Team WoS Importer:2020-04-17